2018
DOI: 10.1155/2018/8460603
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation of Testicular Teratoma to PNET, Adenocarcinoma, and Osteosarcoma with Complete Remission after Surgery and Combination Chemotherapy in a Young Adult Male

Abstract: Mixed germ cell tumors (GCT) with teratoma components can transform into somatic malignancies which can include histologies outside of traditional germ cell lineages. We describe a case of an 18-year-old man with a metastatic testicular GCT with both mature and immature teratoma components containing malignant transformation into multiple histologies including PNET in the primary testicular tumor and osteosarcoma in a separate pulmonary metastatic lesion. Management with targeted chemotherapy resulted in a dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Several studies demonstrated chemoresistance in patients with transformed histology to Cisplatin-based chemotherapy regimens [ 11 , 13 ] that are usually associated with good outcomes in non-transformed malignant germ cell tumors. It was also suggested that chemotherapy should be adapted and targeted against the most aggressive histology for better outcome and disease control [ 5 , 13 ]. However, there is still no consensus regarding the optimal treatment of mixed non-seminomatous GCTs with malignant transformation [ 14 ], and further research is needed to establish clear treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated chemoresistance in patients with transformed histology to Cisplatin-based chemotherapy regimens [ 11 , 13 ] that are usually associated with good outcomes in non-transformed malignant germ cell tumors. It was also suggested that chemotherapy should be adapted and targeted against the most aggressive histology for better outcome and disease control [ 5 , 13 ]. However, there is still no consensus regarding the optimal treatment of mixed non-seminomatous GCTs with malignant transformation [ 14 ], and further research is needed to establish clear treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic type malignant transformations (SMTs) in mixed GCTs is a well-known phenomenon, but is very rare. It occurs in around 3-6% of these tumors and is believed to develop as a result of malignant transformation of the teratomatous components, although other mechanisms might exist such as abnormal differentiation of primordial germ cells [2,5,6]. Tumors accompanied by malignant transformation are more likely to metastasize at presentation and have further aggressive potential than those without this phenomenon [7].…”
mentioning
confidence: 99%
“…Among them, sarcoma and PNET are the most frequent histologies 1 . Cisplatin‐based chemotherapy regimens have proven to be ineffective in the treatment of teratoma with malignant transformation, including PNET 3,4 . We herein describe a case of testicular PNET with para‐aortic lymph node and multiple bone metastases.…”
Section: Introductionmentioning
confidence: 97%
“…Osteosarcoma (OS) is the most common type of bone cancer in both adolescents and young adults [1]. Abnormal epigenetic modifications, such as DNA methylation, have been observed in OS cells [2,3].…”
Section: Introductionmentioning
confidence: 99%